The Techniques of Using Video in Teaching Implemented by English Teacher at SMKN 1 Padang Panjang - Rizki Dian Retno; Yetti Zainil (Universitas Negeri Padang, 2020)
In this research, the researcher discuss about how does the teacher implement techniques in using video as media in teaching English and how effective that techniques using during teaching and learning process in classroom especially for English teachers. The design of this research was the descriptive research. The researcher described and analyzed the phenomenon in the school. English teacher in SMK N 1 Padang Panjang used active viewing technique when the teachers used video as media in teaching English and it is effective to use video as media and active viewing as the technique. The teacher used active viewing technique during teaching and learning process and the teacher used all the steps in indicators for active viewing technique. The students understand about the material that has explained by a video in English teaching. The result of the research finding prove that the teacher has implementation active viewing technique in teaching and learning process at SMK N 1 Padang Panjang, especially in teaching English is running well in implement active viewing technique.Key words: Video, techniques of using video.